Measuring indices of fish community structure in Fisheries Management Area 713 (FMA 713), Indonesia - EKO SRI WIYONO; MUKTI ZAINUDDIN; MEGA LAKSMI SYAMSUDDIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Wiyono ES, Zainuddin M, Syamsuddin ML. 2024. Measuring indices of fish community structure in Fisheries Management Area 713 (FMA 713), Indonesia. Biodiversitas 25: 1857-1866. Understanding the dynamic of the fish community structure over time and space is a fundamental interest and an important component of fisheries science and management. To optimize the utilization of catch species in Fisheries Management Area 713 (FMA 713), the second productive area in Indonesian Waters, we measured the indices of fish community structure in the area. The study analyzed e-log-book fish data introduced by the Ministry of Marine Affairs and Fisheries, Republic of Indonesia (MMAF RI). We studied the composition, productivity, diversity, interaction, and cluster indices to describe the fish community in the study area. The result analysis confirmed that fish composition differed between seasons and reached its highest amount during the west monsoon (WM) season. However, the highest productivity occurred during the east monsoon (EM) season. The diversity of the diversity indices in the study area reached its highest during the WM season and lowest during the second transition (ST) season. In general, there is no significant interaction between most of the catch species. Since the fish community is dynamic seasonally, the fishermen's fishing ground also indicated seasonal movement. During WM and EM seasons, the fishing ground tends to concentrate in the coastal area of Kalimantan. Still, during the transition season, the fishing ground tends to scatter. Therefore, to utilize the fish community results, optimizing fishing was proposed.